Insights on the apparel needs and limitations for athletes with disabilities: The design of wheelchair rugby sports-wear - Braganca, S.; Castellucci, I.; Gil, S.; Matthias, P.; Carvalho, M.; Arezes, P. (Applied Ergonomics, 2018)
No sportswear is available specific for wheelchair rugby. Athletes must use garments designed for abled-bodied people, which is inappropriate and causes discomfort. There is a need for innovation in this area and the athletes are interested in having a product that satisfies their specific requirements. Gloves are the most troublesome sportswear item as they compromise not only the athletes' performance but also their safety. Upper and lower body garments also present some design challenges, especially in terms of fit and body temperature regulation. A set of design recommendations is proposed in order to tackle the problems identified by the athletes based on both the expertise of the team involved in the project and on relevant literature.